Interrelationship of socioeconomic status, food parenting practices, sugar-sweetened beverages intake and physical activity towards anthropometric and biomarkers profile on risk of obesity through path analysis among Iraqi adolescents - Al-Kinani, Abbas Ali Abdulhasan (2025)
Adolescent obesity has emerged as a critical public health challenge in Iraq, where unique post-conflict conditions have accelerated the problem beyond regional norms. With prevalence rates that have tripled over the past decade, Iraqi adolescents face obesity driven by disrupted food systems, limited physical activity opportunities, and strong familial influences on eating behaviors. The country's rapid urbanization and dietary westernization, combined with traditional communal eating practices, create distinct pathways through which obesity develops during this critical developmental period. Understanding these Iraq-specific determinants is essential for creating effective interventions in a setting where public health infrastructure continues to face significant resource constraints. This study aimed to translate and validate Arabic versions of instruments to assess food parenting practices (FPP) and sugar-sweetened beverages (SSBs) and determine the level of sedentary behaviour and physical activity that acted as independent variables. The study further investigated relationships between sociodemographic characteristics and other independent variables with anthropometric measurements (BMI, WHR, WHtR) as an outcome among Iraqi adolescents. The analysis was extended to examine the influence of anthropometric measurements (BMI, WHR, WHtR) with cardiometabolic variables such as lipid profiles, blood pressure, and glycemic control in path analysis. The study was carried out in two phases; phase I emphasized the translation and cultural adaptation of the Adolescent Food Parenting Questionnaire (AFPQ) and the Beverage Intake Questionnaire (BEVQ), followed by psychometric evaluations, including Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Validation analyses confirmed both questionnaires' reliability and validity through acceptable factor structure (EFA/CFA) and strong internal consistency. The BEVQ-A demonstrated high reliability across beverage categories with minimal systematic bias, confirming both instruments' effectiveness for assessing adolescent dietary behaviors. In Phase II, a cross-sectional study design was employed to develop and evaluate a structural path model examining the relationships among key study variables. Data were collected from a sample of 506 adolescents (mean age = 16.53 years, SD = 0.70) using a simple random sampling technique. Statistical analyses were conducted using SPSS version 26, the R package lavaan, and Mplus version 7.4 to ensure robust model estimation and validation. The structural path model identified 45 significant relationships among sociodemographic factors, food parenting practices, dietary behaviours, sedentary behaviour, physical activity, and anthropometric measurements, with satisfactory goodness-of-fit. Standardized Body Mass Index (BMI Z-scores) and Waist-to-Hip Ratio (WHR) showed strong variance (R² > 0.40), while milk calories and snack quantity had weak variance (R² < 0.10). Additionally, the study identified significant associations between anthropometric measurements and cardiometabolic risk factors. Notably, adolescents with greater parental involvement in food choices and healthier dietary behaviors were less likely to be obese. In contrast, higher consumption of sugar-sweetened beverages (SSBs), increased sedentary behavior, and low levels of physical activity were positively associated with obesity and cardiometabolic risks, including elevated blood pressure and unfavorable lipid profiles. These findings highlight the urgent need for family-centered nutrition interventions in Iraq, aimed at fostering healthier home environments and enhancing parental engagement in adolescents’ dietary habits. Additionally, promoting physical activity within schools and communities is critical to counteracting sedentary lifestyles. The study underscores the importance of implementing targeted policies to reduce SSB consumption and promote healthier beverage alternatives. Collectively, these insights offer a strong foundation for evidence-based public health strategies and policy development to address the growing burden of adolescent obesity and its health consequences in Iraq.